Information Production, Banking Industry Structure and Credit Allocation - Gabriella Chiesa (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1998)
Does the removal of intra-state entry barriers increase welfare? Will all banks survive? Will it lead to a consolidation of the banking industry? The experience of credit market deregulation has not been always successful. Credit market liberalisation, via the removal of entry barriers, of limitations of activity and of markets for funding is generally recognised at the origin of banking crises like the American Savings & Loans, the Scandinavian countries' banking crises at the end of the 80's, the Japanese crises not yet resolved and more recently and on a large scale the East-Asian countries. However there are doubts about whether these problems arose because of liberalization per se or rather because of failure of prudential regulation in disciplining banks whose lenders were protected by deposit insurance and State guarantees. Financial markets integration in Europe is still at too an early stage to evaluate, but certainly the very clear process that has emerged is a consolidation of the banking system. Moreover, such a process appears to take place worldwide and somehow be the response to anticipation of future competition. Berger, Kashyap and Scalise (1995) documents a striking amount of consolidation in the American banking industry over the 1979-94 period and attribute this consolidation to the relaxation of intra-state entry barriers, moreover consolidation was favoured by regulators through the easing of the process for approving mergers. footnote Does a concentrated banking industry dominate a fragmented one? This is the question this paper seeks to address.
Keywords: 330